Airborne noise emitted by earth-moving machinery Part 2. Method of measurement at the operator's position in a stationary test condition (BSI, 1987)
Earth-moving equipment, Materials handling equipment, Excavating equipment, Tractors, Loaders, Noise (environmental), Operators (personnel), Drivers (vehicles), Acoustic measurement, Sound intensity, Testing conditions, Stationary, Position